Transboundary management of water resources: the Italian experience in Basilicata and Apulia - Scognamiglio R. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
This paper describes the background and contents of the 'Accordo di Programma' (in the text referred to as 'Agreement') between Apulia, Basilicata and the Italian Ministry of Infrastructure and Transportation (signed on 5th August 1999), in order to solve the critical problem of water scarcity in Apulia. This experience is an excellent example of 'Transboundary Water Management' and how the environmental laws, Italian Galli Act and EU Water Framework Directive, can be implemented to promote economic and social development and assure long-term prospects for sustainable development. Although the 'Agreement' needs further implementation, it represents a positive example of how to address complex situations using a valid methodology with a positive approach in order to share objectives and solve conflicts.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)